Migration Flows in Bosnia and Herzegovina After 1992 - Izet Ibreljic; Salih Kulenovic; Alma Kadusic; Sabahudin Smajic (European Regional Science Association (ERSA), 2006)
Bosnia and Herzegovina is known as migratory dynamic state. Causes for this migration are mainly of political and economical nature. Intensity of migration through Bosnia and Herzegovina in second half of the 19th century and throughout 20th century was cicely intensifying at almost regular time intervals and was caused mainly with political, but also with economical factors. This paper is intended to examine migration streaming in Bosnia and Herzegovina in the last decade of 20th and the beginning of the 21st century. It examines the forced migration generated by war that was raging in the state in the period of 1992-1995, as well as the post-war migration caused by economical and political factors, but it also examines the return of displaced people to their homes after the war ending. By using all available domestic and foreign written sources in this field, authors will give consideration to entire series of questions that are intruding into these issues. Analysis of the consequences of former migration flows and probability of their reduction, that is, defining the vision of the state in these new conditions, certainly dominates this paper among all other things.
Keywords: 330